Cowpea (Vigna unguiculata L. Walp.) Metabolomics: Osmoprotection as a Physiological Strategy for Drought Stress Resistance and Improved Yield - Goufo, Piebiep; Moutinho-Pereira, José M.; Jorge, Tiago F.; Correia, Carlos M.; Oliveira, Manuela R.; Rosa, Eduardo A. S.; António, Carla; Trindade, Henrique (Frontiers in Plant Science, 2017)
Plants usually tolerate drought by producing organic solutes, which can either act as compatible osmolytes for maintaining turgor, or radical scavengers for protecting cellular functions. However, these two properties of organic solutes are often indistinguishable during stress progression. This study looked at individualizing properties of osmotic adjustment versus osmoprotection in plants, using cowpea as the model species. Two cultivars were grown in well-watered soil, drought conditions, or drought followed by rewatering through fruit formation. Osmoadaptation was investigated in leaves and roots using photosynthetic traits, water homoeostasis, inorganic ions, and primary and secondary metabolites. Multifactorial analyses indicated allocation of high quantities of amino acids, sugars, and proanthocyanidins into roots, presumably linked to their role in growth and initial stress perception. Physiological and metabolic changes developed in parallel and drought/recovery responses showed a progressive acclimation of the cowpea plant to stress. Of the 88 metabolites studied, proline, galactinol, and a quercetin derivative responded the most to drought as highlighted by multivariate analyses, and their correlations with yield indicated beneficial effects. These metabolites accumulated differently in roots, but similarly in leaves, suggesting a more conservative strategy to cope with drought in the aerial parts. Changes in these compounds roughly reflected energy investment in protective mechanisms, although the ability of plants to adjust osmotically through inorganic ions uptake could not be discounted.